2003
DOI: 10.1051/forest:2003043
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual mobility of nitrogen between beech rings: a labelling experiment

Abstract: -Nitrogen concentration [N] and isotopic composition (δ 15 N) in annual growth rings of 16-year-old beech trees (Fagus sylvatica L.) were measured before and after treatment of wood using organic solvents. The trees, grown under field conditions in Northeastern France, were labelled with 15 N-enriched urea solution at leaf level for three successive years (1993, 1994 and 1995), and were sampled in 2001. δ 15 N values in this experiment ranged from -4 to -7‰ for non-labelled tree. Labelling resulted in markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 24 publications
8
51
2
Order By: Relevance
“…we might expect that, compared with "old" wood, tissues acting as a sink of the N recycled (needles, bark and recently formed wood) should have higher N concentration and: a) higher δ 15 N values if mobile N is 15 N-enriched, as compounds chemically extracted by Elhani et al (2003), Hart and Classen (2003) and Bukata and Kyser (2005); or b) lower δ 15 N values if products released and reallocated during lignification were 15 N-depleted compared with the source (Evans 2001). Results of the present study support the latter expectation; consequently, without more experimental data, it seems that we should be cautious in considering that proposed chemical extractions are removing the more physiologically mobile N compounds from wood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…we might expect that, compared with "old" wood, tissues acting as a sink of the N recycled (needles, bark and recently formed wood) should have higher N concentration and: a) higher δ 15 N values if mobile N is 15 N-enriched, as compounds chemically extracted by Elhani et al (2003), Hart and Classen (2003) and Bukata and Kyser (2005); or b) lower δ 15 N values if products released and reallocated during lignification were 15 N-depleted compared with the source (Evans 2001). Results of the present study support the latter expectation; consequently, without more experimental data, it seems that we should be cautious in considering that proposed chemical extractions are removing the more physiologically mobile N compounds from wood.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that the removal of extractives is necessary in 15 N-labelling studies (Elhani et al 2003), but removal of extractives may not be necessary at natural δ 15 N. Hart and Classen (2003) found that the removal of extractives from the wood reduced their δ 15 N value, but the change was fairly small and consistent among unlabelled trees (about 2 to 3 ‰). In spite of wood N content being reduced by 36% after removal of mobile compounds, Elhani et al (2003) reported a δ 15 N decrease less than 0.4 ‰ for most annual rings, a figure actually close to analytical precision of δ 15 N in wood (st.dev. typically around 0.3 ‰); moreover, they only found significant differences between extracted and non-extracted wood in 4 out 14 rings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizer and tracer studies recovered labeled N in rings formed prior to N application, indicating that trees redistribute N from recently formed rings into older rings via rays (Nommik 1966;Mead and Preston 1994;Schleppi et al 1999;Elhani et al 2003). In fact, studies have shown N mobility throughout all plant tissues over the course of numerous growing seasons, indicating that N redistribution is a continual process (Mead and Preston 1994) (Elhani et al 2003;Kwak et al 2009).…”
Section: To Extract or Not Extractmentioning
confidence: 99%
“…This is a key issue for all wood δ 15 N studies (not just fertilizer and tracer studies), as significant translocation of N across rings could mask or remove signals of environmental N availability. Under N additions with high δ 15 N signatures, rings corresponding to the years of N addition often show a clear and dramatic peak (Elhani et al 2003) although the peak may be delayed by 1-2 years after the fertilization treatment (Hart and Classen 2003). When N additions are highly enriched (high δ 15 N), ring δ 15 N shows a dramatic increase at the onset of N addition and a slow decline over several years following the initial peak (Elhani et al 2003, Hart andClassen 2003).…”
mentioning
confidence: 99%